PERAN JAKSA AGUNG REPUBLIK INDONESIA TERHADAP PEMBENTUKAN DAN PELAKSANAAN TUGAS TIM PENGAWALAN, PEMERINTAH DAN PEMBAGUNAN DAERAH - Muhammad Taufiqurrahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
This discussion dealt with The Role of the Attorney General of the Republic of Indonesia in the Formation and Implementation of the Duty of the Guards, Safeguards of Government and Regional Development Team (TP4D). The problems of the study discussed in this research were what the legal arrangement of the Guards, Safeguards of Government and Regional Development Team (TP4D) was and what the role of the prosecutors in Guards, Safeguards of Government and Regional Development Team (TP4D) was. The research method used with the type of research used was empirical legal research. Empirical legal research is a legal research method that functions to be able to see the law in the real sense and examine how the law works in a community environment. The specification of this research is descriptive, with the intention to describe the existing conditions by using scientific research methods and solving problems based on data and facts collected as they were at the time the research was conducted. The conclusion in the discussion was that the President Instruction No. 1 of 2016 concerning the Acceleration of the Implementation of National Strategic Projects was not only addressed to the Ministers of the Work Cabinet, Cabinet Secretary, the Chief of the President Staff, the Heads of Non-Ministry Government Agencies, Governors and Regents / Mayors, but also instructed to the General Attorney of the Republic of Indonesia and the Head of the Indonesian National Police. To fight the stigma of criminalizing the policy that made the bureaucratic officials and businessmen afraid and hesitant in making decisions on accelerating the development and the strategies of national development programs, the Guards, Safeguards of Government and Regional Development Team (TP4D) was formed based on the decision of the Attorney General of the Republic of Indonesia No. KEP-152 / A / JA / 10/2015 dated October 1, 2015 concerning the establishment of the Guards, Safeguards of Government and Regional Development Team (TP4D) of the Republic of Indonesia which have the duties: to guard, secure and support the success of the running of the government and development through prevention / preventive and persuasive efforts in the jurisdiction of the Prosecutor's Office. While it was expected that the budget absorption was running normally for the benefit of the programs of national development. It was expected that resolutions of the existing problems with policies and officials will use the Government Administration process in accordance with the provisions of Law No. 30 of 2014 concerning Government Administration,